Efficacy of zinc supplementation for the treatment of dysmenorrhoea: a double-blind randomised controlled trial - Hillary I. Obiagwu; George U. Eleje; Nworah J.A. Obiechina; Betrand O. Nwosu; Gerald O. Udigwe; Joseph I. Ikechebelu; Joseph O Ugboaja; Chukwuemeka C. Okoro; Ifeanyi O. Okonkwo; Ayodele O. Okwuosa; Charlotte B. Oguejiofor; Chisom G. Chigbo; et al. (Journal of International Medical Research, 2023)
Objectives To determine the efficacy of zinc sulfate supplementation in managing dysmenorrhoea. Methods In total, 103 high school students were randomised into an experimental arm (52 students) and a control arm (51 students) and received 40-mg zinc sulfate or placebo, respectively, over three cycles. Primary outcome measures were the mean Visual Analogue Scale score, which measured pain over three cycles, and the frequency of nausea and vomiting. Secondary outcomes were the use of additional analgesics and the frequency of allergic reactions. Results Fifty participants were analysed in each group. Mean pain scores were not significantly different between the groups before administering zinc sulfate therapy. Following the intervention, the mean pain scores for the treatment (2.80 ± 2.28) and placebo (3.48 ± 2.85) groups were not significantly different in the first cycle; however, scores in the treatment group were significantly better in the second (2.56 ± 1.97 vs 3.80 ± 2.77) and third (1.95 ± 1.72 vs 3.95 ± 2.82) cycles. No significant differences were observed between the groups in the nausea and vomiting incidence and the requirement for additional analgesics. Conclusions Zinc sulfate reduces dysmenorrhoea severity with minimal or no adverse effects, especially with more than one cycle of usage. Trial Registration Number: PACTR202105843292338. The trial is publicly available and was registered at www.pactr.org on 25 May 2021.